Synopsis of Approaches to Welfare and of Green Growth Concepts Currently under Discussion - Gerd Ahlert; Bernd Meyer; Roland Zieschank; Hans Diefenbacher; Hans G. Nutzinger (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2013)
This paper is part of the research project Cornerstones of an ecologically sustainable welfare concept as a basis for eco-political innovation and transformation processes funded by the German Ministry of Environment. The main aim is to identify differentiated and exemplary starting points for an eco-politically viable and measurable concept of sustainable welfare. The synopsis presented here concentrates on the systematic evaluation of current discussions on alternative approaches to welfare, ecologically oriented welfare doctrines and strategies on the basis of a consistent matrix of questions. Key points of a sustainable welfare model in ten theses are formulated. Such a model should illustrate the environmental policy by showing its effect on peoples welfare and the use of the natural world and should assist national environmental policy in its decision-making.
Keywords: I31; Q58; 330; sustainable welfare; synopsis; welfare doctrines; model